Groundwater balance and conservation under different water pricing and agricultural policy scenarios: A case study of the Hamadan-Bahar plain - Balali, Hamid; Khalilian, Sadegh; Viaggi, Davide; Bartolini, Fabio; Ahmadian, Majid (Ecological economics, 2011)
Government subsidies for agricultural activities in recent decades have encouraged farmers of Hamadan-Bahar plain to extend the number of wells and irrigated farms, with no consideration of groundwater resource conservation. As a result, the level of the groundwater table has decreased continuously in this area, threatening the life of groundwater aquifer. The objective of the study is to analyze the impacts of irrigation water pricing and agricultural policy scenarios on aquifer conservation by considering the dynamic relations between aquifer groundwater balance and the agriculture sector. For this purpose a combination of simulation and optimization techniques is considered in a dynamic framework. Firstly, dynamic treatments of groundwater and the main factors affecting the balance of studied aquifer are simulated. Then, optimization behaviour of agriculture sector related to farmers' decision-making processes is defined on the time horizon. Thereafter all of the equations are used simultaneously by a non-linear dynamic programming method, which maximize present value of gross margins of agriculture sector subject to groundwater constrains and other input limitations. The analysis of the results indicates that water pricing by itself can considerably reduce the agricultural demand for aquifer groundwater in the Hamadan-Bahar plain. ► We modelled groundwater use by farmers in Bahar plain and groundwater dynamics. ► The model was used to simulate different policy scenario options. ► Water pricing can reduce the use of groundwater by irrigated agriculture. ► Price elasticities along the groundwater demand curve vary considerably. ► Instruments in addition to pricing schemes are needed to reduce water.